[OP.2D.01] ANGIOTENSIN-(1–7) IMPROVES ENDOTHELIAL FUNCTION AND THE DEVELOPMENT OF ATHEROSCLEROSIS THROUGH THE MAS RECEPTOR. (September 2016) - Grave, K.; Yang, G.; Hering, L.; Potthoff, S.A.; Schwandt, C.; Iktas, G.; Rump, L.C.; Stegbauer, J.
Abstract : Objective: Recently, we have shown that chronic Ang-(1–7) treatment acting through the Mas receptor improves vascular dysfunction in atherosclerotic apolipoprotein E-deficient (apoE-/-) mice by increasing NO bioavailability. To test whether deletion of the Mas receptors aggravates atherosclerosis and to examine the underlying mechanism, we generated apoE/Mas-KO mice. Design and method: 12 weeks old ApoE-KO and apoE/Mas-KO mice fed on a lipid-rich Western diet were treated via osmotic minipumps with either saline or Ang-(1–7) (82 μg/kg/h) for 6 weeks. Aortae were stained with red oil and quantified for atherosclerosis. To examine whether Ang-(1–7) modulates endothelial function and the development of atherosclerosis through a NO dependent mechanism, flow mediated dilation (FMD) was measured in vivo in unconscious mice. Moreover, 8 weeks old apoE-KO mice treated with L-NAME (20 mg/kg/d) were infused either with Ang-(1–7) or saline for 6 weeks. Tissue nitrite, a marker for NO generation was measured by HPLC. Results: Endothelial-dependent vasorelaxation and atherosclerosis was significantly impaired in Mas/apoE-KO mice compared to apoE-KO (relative lesion area of the aortic arch: 38.7 ± 3.0 vs. 25.4 ± 2.0%; P < 0.01; specific lesion area 11.7 ± 0.9 vs. 8.1 ± 1.0 mm 2 P < 0.01). Moreover, nitrotyrosin and urinary 8-Isoprostane levels, both markers for oxidative stress were significantly increased in Mas/apoE-KO compared to apoE-KO mice. In contrast, chronic Ang-(1–7) treatment improves FMD and attenuated atherosclerotic lesion in apoE-KO (11.1 ± 2.6% vs. 25.4 ± 2.0, P < 0.01 and 3.1 ± 0.8 mm 2 vs. 8.1 ± 1.0, P < 0.01) but not in apoE/Mas-KO mice (38.7 ± 3.0 vs. 38.0 ± 14.2% and 11.7 ± 0.9 vs. 11.4 ± 5.0 mm 2 ). Additionally, aortic nitrite content was increased in Ang-(1–7) treated apoE-KO compared to untreated apoE-KO mice (180 ± 31 vs. 311 ± 47 μM/g, P < 0.05). L-NAME treatment increased blood pressure (BP) and reduced aortic nitrite content significantly compared to sham-treated apoE-KO mice. However, Ang-(1–7) treatment did not affect BP (127 ± 3 vs. 128 ± 3 mmHg), aortic nitrite (861 ± 16 vs. 1004 ± 174 μM/g) content and the development of atherosclerosis in L-NAME treated apoE-KO mice. Conclusions: In conclusion, our findings indicate that Ang-(1–7) improves atherosclerosis via Mas receptor activation. Moreover, these effects seems to mediated through a NO-dependent mechanism as Ang-(1–7) failed to affect atherosclerosis in L-NAME treated mice.